HUTAN DAN PENGENDALIAN BAN JIR (SEBUAH TANTANGAN BAGI PROFESI RIMBAWAN) - Triwanto, Joko (Jurnal Bestari, 2008)
Forestry seems to be unimportant subject, while it is important capital to prevent flood, global warming, and provides plentiful natural resources. Human became the cause of nature destructions. Therefore, the action to prevent disaster enabled the decision makers to work accurately to manage the forest well using minimum budget. Management on water and sediment on the river need to be prepared thoroughly and made in integrated way among sectors and regions.